Age of onset by sex in schizophrenia: Proximal and distal characteristics. (July 2022) - Selvendra, Ajit; Toh, Wei Lin; Neill, Erica; Tan, Eric J.; Rossell, Susan L.; Morgan, Vera A.; Castle, David J.
Abstract: Background: Earlier schizophrenia onset in men relative to women has been a consistent finding in the literature, but a nuanced understanding of underlying reasons remains elusive. Further consideration should be given to factors associated with sex differences in age of onset. Method: Participants with schizophrenia were derived from the 2010 Australian Survey of High Impact Psychosis ( n = 857). The SHIP survey constituted a representative, population-based study of almost 1.5 million Australian adults seen at various mental health services, and assessed personal health information, psychiatric comorbidities as well as psychosis illness and treatment. Hierarchical clustering was employed to identify age of onset by sex. Within-sex comparisons on distal and proximal factors affecting age of onset were conducted. Results: Using modal age, two and three clusters were respectively found in men (early versus late onset) and women (early versus mid versus late onset). Early onset groups in both sexes had an increased family history of psychosis compared to older onset, but other risk factors were not consistent across the sexes. Less premorbid impairment was noted in females with middle to later onset schizophrenia. Conclusion: These findings further inform our understanding of the pathogenesis of schizophrenia. Added explorations of trends in older onset schizophrenia cohorts is especially important.